Exploring Anomalous Relaxation Models in Prime Number Distribution and Their Relevance to Sustainable Development Education - Abdulqader S.A.; Al_Barazanchi I.I.; Jaaz Z.A.; Sekhar R.; Shah P.; Malge S. (International Information and Engineering Technology Association, 2025)
Mathematical frameworks termed anomalous relaxation models are used to characterize the distribution of prime numbers in an unconventional way. Many scholars need clarification on the challenges with prime numbers (PN), because of their mysterious and complicated qualities because it is challenging to build a model that characterizes the relaxed distribution of PN in a collection of all natural numbers. Although certain qualitative methods, like Riemann's Theory, exist to the best of the educational knowledge can characterize the distribution of the prime numbers, the law controlling the distribution of the PN is unclear, and the correct model needs to be established. The distribution of prime numbers is obtained in the current work for the first time using the anomalous relaxation model with the fractional derivative. The new model matches well with the data of PN, according to comparisons with Riemann's Theory and the PN Theory of sustainable development education. ? (2024) The authors. This article is published by IIETA and is licensed under the CC BY 4.0 license (http://creativecommons.org/licenses/by/4.0/).